Explodability criteria for the neutrino-driven supernova mechanism - Maltsev, Kiril; Schneider, Fabian; Mandel, I.; Müller, B.; Heger, Alexander; Röpke, Friedrich; Laplace, E. (Astronomy and astrophysics, 2025)
Massive stars undergoing iron core-collapse at the end of their evolution terminate their lives either as successful or failed supernovae (SNe). The physics of core-collapse supernovae (CCSNe) is complex and understanding it requires computationally expensive simulations. Therefore, using these simulations to predict CCSN outcomes over large, densely sampled parameter spaces of SN progenitors (as is needed, e.g., for population synthesis studies) is not feasible. To remedy this situation, we present a set of explodability criteria that allow us to predict the final fates of stars by evaluating multiple stellar structure variables at the onset of core collapse. These criteria are calibrated to predictions made using a semi-analytical SN model, when evaluated over a set of ∼3900 heterogeneous stellar progenitors (comprised of single stars, binary-stripped and accretor stars). Over these, the explodability criteria achieve a > 99% agreement with the semi-analytical model. We test these criteria on 29 state-of-the-art 3D CCSN simulation outcomes from two different groups. Furthermore, we find that all explodability proxies needed for our pre-SN structure-based criteria have two distinct peaks and intervening valleys as a function of the carbon-oxygen (CO) core mass, M CO, coinciding with failed and successful SNe, respectively. The CO core masses of explodability peaks shift systematically with metallicity, Z , as well as with the timing of the hydrogen-rich envelope removal via binary mass transfer. Using the criteria and the systematic shifts, we identify critical values in M CO that define windows over which black holes form by direct collapse. With these findings, we formulate a CCSN recipe based on M CO and Z that is applicable for rapid binary population synthesis and other studies. Our explodability formalism is consistent with observations of Type IIP, IIb, Ib and Ic SN progenitors and it partially addresses the missing red supergiant problem by direct black hole formation.
Online veröffentlicht: 29. Juli 2025
Gesehen am 14.01.2026